Photocatalytic Simulation of Phenol Waste Degradation Using Titanium Dioxide (TiO2) P25-Based Photocatalysts - Wibawa Hendra Saputera; Jeffry Jaya Pranata; Reynaldo Jonatan; Pramujo Widiatmoko; Dwiwahju Sasongko (Journal of Engineering and Technological Sciences, 2023)
Phenol waste treatment is vital in industries such as polymer production, coal gasification, refinery, and coke production. Photocatalytic technology using semiconductor materials offers an effective and ecofriendly approach to degrade phenol. TiO2 P25 is a widely used photocatalyst, known for its cost-effectiveness, favorable optical and electronic properties, high photoactivity, and photostability. The PHOTOREAC application, a recently developed MATLAB-based software, simulates the degradation of phenol using visible light. A study that combines existing literature and research revealed that pH significantly influences photocatalytic activity, with an optimum pH of 7 for TiO2 P25-mediated phenol degradation. The recommended photocatalyst concentration ranged from 0 to 10 g/L for reactor volumes between 25 and 60 mL, and from 0 to 5 g/L for 100-mL reactors. Phenol wastewater volume and light intensity also impact degradation efficiency. Adequate oxygen supply, achieved through bubbling and mixing, is essential for the formation of radical compounds. The Ballari kinetic model proved to be the most suitable for phenol degradation with TiO2 P25. Thus, by combining PHOTOREAC simulations with experimental data, the treatment process could be optimized to achieve higher degradation efficiency and estimate the treatment time for specific waste degradation levels. This study contributes to the advancement of phenol waste treatment and the development of improved photocatalytic wastewater treatment technologies.